Aandacht voor zingeving: Context en praktijk van geestelijke verzorging in het aardbevingsgebied van Groningen - de Kraker-Zijlstra, Anieljah (NTT, 2021)
Attention for Meaning-Making Processes: Context and Practice of Spiritual Care in the Earthquake Area of Groningen In the North of the Netherlands spiritual caregivers have been employed to respond to the social and personal needs resulting from human induced earthquakes. In the Netherlands knowledge on spiritual care in times of disasters is limited. Central to the present study are two questions: How is spiritual care being put into practice in Groningen? And how do the spiritual caregivers cooperate with others in psychosocial care and in the social domain? This article describes the context, the reasons spiritual care came to be provided and the primary activities of the spiritual caregivers during their initial year of practice.